2014
DOI: 10.1016/j.earlhumdev.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Postural complexity differs between infant born full term and preterm during the development of early behaviors

Abstract: Background and Aims Postural control differs between infants born preterm and full term at 1–3 weeks of age. It is unclear if differences persist or alter the development of early behaviors. The aim of this longitudinal study was to compare changes in postural control variability during development of head control and reaching in infants born preterm and full term. Methods Eighteen infants born preterm (mean gestational age 28.3±3.1 weeks) were included in this study and compared to existing data from 22 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 24 publications
2
33
0
2
Order By: Relevance
“…14 Although group differences exist, the general patterns of changes in postural complexity are similar for infants born full term and infants born preterm. 18 All 3 infants in this case series demonstrated some changes in postural complexity over time, between conditions, or both, and these changes may have been related to their developmental outcomes. Infant 1's optimal postural complexity in early development supported her use of action and perception to learn, even with significant motor impairments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14 Although group differences exist, the general patterns of changes in postural complexity are similar for infants born full term and infants born preterm. 18 All 3 infants in this case series demonstrated some changes in postural complexity over time, between conditions, or both, and these changes may have been related to their developmental outcomes. Infant 1's optimal postural complexity in early development supported her use of action and perception to learn, even with significant motor impairments.…”
Section: Discussionmentioning
confidence: 99%
“…16 Infants born preterm used more repetitive postural sway patterns at an adjusted age (AA; ie, chronological age minus weeks preterm) of 1 to 3 weeks and demonstrated less adaptive postural control strategies while learning to control their head in the midline position and during a reaching task. 17,18 Evidence on the role of postural complexity in optimal health, early development, and developmental disabilities suggests that alterations in postural complexity may be predictors of disability. 16,19 A better understanding of the role of postural complexity in the prediction of disability may support the identification of clinically useful tools for predicting motor disability.…”
Section: Complexity In Development and Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even at term-corrected age, the brains in preterm infants may show compromised gray matter volume and altered developmental trajectory (1), probably explaining delayed neonatal arousal (2,3) and immature neuromuscular function and brain electroencephalography (4). In more longterm studies, preterm infants have shown reduced postural complexity (5) and lowered motor function (6), potentially persisting until school age (7), or even into adulthood (8). Thus, early impairment of physical locomotion in preterm infants may have long-term consequences.…”
mentioning
confidence: 99%